BAKTI SOSIAL SEBAGAI UPAYA KEGIATAN MENUMBUHKAN KEPEMIMPINAN DAN EMPATI BAGI MAHASISWA - Nugroho, Arif Julianto Sri; Haris, Abdul; Jati, Agung Nugroho; Kuntaryanto, Oki; Marjukah, Anis; Prasetyo, Jarot; Supratikno (WIDHARMA - Jurnal Pengabdian Widya Dharma, 2023)
As the lecturers of higher education, what we can do is to contribute back to society. We need to apply the rule of leadership, empathy, and also give and take. We believe that even though we are not giving them much, but it is better than no right. It may sounds like there’s no innovation, we do admit that. However we thought that the outcome we get is far more important than innovation that we do not even have any ideas about leadership and empathy.